Laparoscopic right hemicolectomy for metachronous ascending colon cancer with preservation of an ileal conduit constructed after previous radical cystectomy for bladder cancer. Issue 2 (May 2015) - Okoshi, Kae; Hasegawa, Suguru; Murakami, Teppei; Yamada, Masahiro; Hida, Koya; Kawada, Kenji; Sakai, Yoshiharu
Abstract: A 79‐year‐old woman who had undergone laparoscopic radical cystectomy and ileal conduit construction for bladder cancer 4 years earlier presented to our hospital with anemia. We diagnosed advanced ascending colon cancer (cT4bN2M1) and documented tumor regression after six courses of folinic acid, 5‐fluorouracil, and oxaliplatin therapy. We then performed laparoscopic right hemicolectomy. Intraoperatively, we found that the right colic artery was the feeding artery of the tumor, whereas the ileocolic artery, which was the main feeder of the conduit, was not. We performed lymph node dissection along the surgical trunk with central vascular ligation of the right colic artery and the right branch of the middle colic artery while preserving the ileal conduit and its blood supply (ileocolic artery and ileal branches). The postoperative course was uneventful, and the patient remains well and cancer‐free 2 years after colonic surgery. We believe that this is the first report of laparoscopic right colectomy in a patient with an ileal conduit.